2014
DOI: 10.1080/01457632.2014.897576
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady Mixed Convective Flow Confined between Vertical Wavy Wall and Parallel Flat Wall Filled with Porous and Fluid Layer

Abstract: The unsteady mixed convective flow in a long vertical channel containing porous and fluid layer bounded by a smooth and corrugated wall is studied. Nonlinear equations governing the motion have been solved by linearization technique wherein the flow is assumed to be in two parts: a mean part and a perturbed part. Exact solutions are obtained for the mean part, and the perturbed part is solved using long wave approximation. Separate solutions are matched at the interface using suitable matching conditions. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Umavathi et al, [16] studied numerically the unsteady flow and heat transfer in a horizontal channel and found that raising the thermal conductivity ratio lowers temperature rise. Later, Umavathi and Shekar [17] investigated the unsteady combined convection flow in a long vertical channel including a porous and fluid layer, which was surrounded by a smooth and corrugated wall. It was discovered that the Grashof number, width ratio, and conductivity ratio all contribute to the promotion of velocity parallel to the flow direction.…”
Section: Introductionmentioning
confidence: 99%
“…Umavathi et al, [16] studied numerically the unsteady flow and heat transfer in a horizontal channel and found that raising the thermal conductivity ratio lowers temperature rise. Later, Umavathi and Shekar [17] investigated the unsteady combined convection flow in a long vertical channel including a porous and fluid layer, which was surrounded by a smooth and corrugated wall. It was discovered that the Grashof number, width ratio, and conductivity ratio all contribute to the promotion of velocity parallel to the flow direction.…”
Section: Introductionmentioning
confidence: 99%